Implementation of the DoD Diversity and Inclusion Strategic Plan - Nelson Lim,,, Abigail Haddad, Lindsay Daugherty (RAND Corporation, 2014)
The Department of Defense (DoD) published its Diversity and Inclusion Strategic Plan in 2012. This report aims to discuss issues that DoD needs to consider in its implementation of the strategic plan and to provide a framework that DoD can use to organize its strategic initiatives. The framework categorizes the strategic initiatives specified in the DoD Diversity and Inclusion Strategic Plan along three key dimensionsâ€”compliance,communication, and coordination (â€œthethree Csâ€)â€”and prioritizes them across timeâ€”short, medium, and long term. The framework can help all DoD components work toward the vision described in the strategic plan in a deliberate, synchronized effort by complying with current laws, regulations, and directives; communicating effectively to internal as well as external stakeholders; and coordinating efforts to ensure continuing change. This work is intended to supplement the final report of the Military Leadership Diversity Commission (MLDC), From Representation to Inclusion: Diversity Leadership for the 21st-Century Military. The primary author of this RAND report was the research director of the MLDC effort, yet this report does not necessarily reflect the opinions of the MLDC commissioners. This work also draws from earlier RAND work, Planning for Diversity: Options and Recommendations for DoD Leaders, by Nelson Lim, Michelle Cho and Kimberly Curry Hall(Santa Monica, Calif.: RAND Corporation, MG-743-OSD, 2008); current organizational management literature; DoD strategic documents;and discussions with senior staff of the DoD Office of Diversity Management and Equal Opportunity (ODMEO). The research was sponsored by the Office of Personnel and Readiness in the Office of the Secretary of Defense and conducted within the Forces and Resources Policy Center of the RAND National Defense Research Institute, a federally funded research and development center sponsored by the Office of the Secretary of Defense, the Joint Staff, the Unified Combatant Commands, the Navy, the Marine Corps, the defense agencies, and the defense Intelligence Community. For more information on the RAND Forces and Resources Policy Center, see http://www.rand.org/nsrd/ndri/centers/frp.html or contact the director (contact information is provided on the web page).